THE EFFECT OF BRAND EXPERIENCE AND BRAND IMAGE ON THE WILLINGNESS TO PAY A PRICE PREMIUM MEDIATED BY BRAND LOVE ON CUSTOMERS OF A COFFEE SHOP - Erwin; Melva Hermayanty Saragih (Suluh Adiluhung Publisher (SAPub), 2025)
This study aims to examine the influence of brand experience and brand image on willingness to pay a price premium, with brand love as a mediating variable among customers of a coffee shop in Medan. A quantitative approach was employed, with data collected through questionnaires distributed to 131 customers. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4. The results show that brand image has a positive and significant effect on willingness to pay a price premium, while brand experience does not. Both brand experience and brand image have positive and significant effects on brand love. Furthermore, brand love significantly influences willingness to pay a price premium. However, brand love does not mediate the relationship between brand experience and willingness to pay a price premium, nor between brand image and willingness to pay a price premium. These findings offer valuable implications for coffee shop marketing strategies in building strong and emotional brand perceptions to enhance customers’ willingness to pay higher prices.